A Canary in the Coal Mine: Reproductive Health and Cardiovascular Disease in Women - Quinn, Molly M.; Cedars, Marcelle I. (Seminars in Reproductive Medicine, 2017)
Cardiovascular disease (CVD) is the leading cause of mortality in women in the United States. Compared with age-matched men, premenopausal women are protected against CVD, yet this difference dissipates after menopause. Hypogonadism underlies the shared increased CVD risk seen in menopause, primary ovarian insufficiency (POI), and hypogonadotropic hypogonadism. Early menarche and PCOS have also been associated with CVD risk factors, highlighting the importance of mediators other than deficient estrogen in the underlying etiology of this female-specific increased risk. Pregnancy complications such as preeclampsia, gestational diabetes, and preterm delivery are also associated with subsequent CV disease and offer early opportunities for the identification of risk. Preliminary evidence suggests a common underlying vascular pathology for ovarian aging and pregnancy complications such as preeclampsia. Research is needed to understand the shared pathophysiology of these female-specific risk factors for CVD and target interventions to change outcomes.
Keywords: cardiovascular disease; menopause; ovarian aging; PCOS; preeclampsia